2017
DOI: 10.1021/acs.analchem.7b03569
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Nanodisc Scaffold Proteins for Native Mass Spectrometry

Abstract: Lipoprotein nanodiscs are ideally suited for native mass spectrometry because they provide a relatively monodisperse nanoscale lipid bilayer environment for delivering membrane proteins into the gas phase. However, native mass spectrometry of nanodiscs produces complex spectra that can be challenging to assign unambiguously. To simplify interpretation of nanodisc spectra, we engineered a series of mutant membrane scaffold proteins (MSP) that do not affect nanodisc formation but shift the masses of nanodiscs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(99 citation statements)
references
References 29 publications
3
87
0
1
Order By: Relevance
“…Although the SoftMax function pushes the algorithm towards a single charge state for each data point, it allows for overlapping peaks where a data point can be legitimately assigned to more than one charge state. Finally, a spectrum of POPC nanodiscs with mixed membrane scaffold protein belts was investigated ( Figure 2g) [8]. Although well-resolved, this spectrum contains many overlapping peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Although the SoftMax function pushes the algorithm towards a single charge state for each data point, it allows for overlapping peaks where a data point can be legitimately assigned to more than one charge state. Finally, a spectrum of POPC nanodiscs with mixed membrane scaffold protein belts was investigated ( Figure 2g) [8]. Although well-resolved, this spectrum contains many overlapping peaks.…”
Section: Resultsmentioning
confidence: 99%
“…110,111 A first study explored nanodiscs, bicelles and amphipols for native MS and showed that indeed the native oligomeric states of several integral membrane proteins were preserved in nanodiscs and bicelles while they differed from those obtained from detergent micelles or amphipols. 112 In particular, nanodiscs were therefore examined in detail; the complex and heterogeneous mass spectra further induced improvements in spectral deconvolution, [113][114][115][116] sample preparation [117][118][119] and method optimisation. 119,120 These improvements allowed, for instance, monitoring the insertion and oligomer assembly in the lipid bilayer.…”
Section: Unravelling the Architecture Of Membrane Protein Assembliementioning
confidence: 99%
“…Such analyses could be leveraged to further understand how MPs interface with their surrounding lipid environment. Empty nanodiscs have also been studied by native MS allowing, for example, the precise lipid composition to be determined [117][118][119][120].…”
Section: Disc Technologies For Native Msmentioning
confidence: 99%